2020
DOI: 10.1115/1.4048723
|View full text |Cite
|
Sign up to set email alerts
|

Improving Precision in Aluminum Alloy Machining Due to the Application of Diamond-Like Carbon Thin Film

Abstract: Cutting precision is extremely affect by a phenomenon known as built-up edge (BUE) that occurs on tungsten carbide tools during low cutting speed of aluminum alloy. BUE is responsible for early tool breakage due to excessive material build-up from the machined part on the cutting face, leading to problems of shape irregularity and tool-tip breakage. Thus, Diamond-like Carbon was deposited and tested to verify cutting precision in aluminum alloy by using tungsten carbide tools. The characterizations of the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Accordingly, the surface roughness of the hole in the FRP layer deteriorates compared to that in the metal layer. Additionally, FMLs based on aluminum alloys such as CARALL, ARALL, and GLARE tend to produce an excessive built-up edge (BUE) on the drill tool, leading to a higher rate of tool life deterioration [15]. This results in inadequate chip evacuation, and the chips left behind tend to erode the fibers and metal surface, consequently diminishing the surface finish of drilled holes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the surface roughness of the hole in the FRP layer deteriorates compared to that in the metal layer. Additionally, FMLs based on aluminum alloys such as CARALL, ARALL, and GLARE tend to produce an excessive built-up edge (BUE) on the drill tool, leading to a higher rate of tool life deterioration [15]. This results in inadequate chip evacuation, and the chips left behind tend to erode the fibers and metal surface, consequently diminishing the surface finish of drilled holes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Vilches et al (2021) found that indirect wear from adhesion to built-up edge and built-up layer are the main factors leading to the cermet tool wear in the turning of UNS A97075 Alloy. Generally, the build-up was mainly caused by the thermo-mechanical effects during machining, and greatly influenced the cutting performance in terms of surface quality, cutting force, chip formation and tool wear (Pálmai 2012, Chowdhury et al 2021, Silva et al 2021.…”
Section: Introductionmentioning
confidence: 99%